Model Runtut waktu untuk Peramalan Indeks Kekeringan Daerah Lombok Utara - Humairo Saidah; I Wayan Yasa; Muh. Bagus Budianto; Syamsul Hidayat; I.D.G Jayanegara (LPPM Universitas Mataram, 2019)
PDSI is the drought index method which has good accuracy to be applied in Lombok Island. However, this method is only able to hindcast the drought without any procedure to predict the drought index in the future. So, this model aims to recognize the characteristics of drought in North Lombok for early mitigation and anticipating drought disasters purposes in this region. The results obtained from this study are that the drought pattern in North Lombok has the SARIMA model of (0,1,2) (0,1,1)12. The drought in North Lombok mainly occurs between May-October with an increasing of drought index tends for over last 20 years.